“God is Dead”: Envisaging a New Theology after Nietzsche's Obituary - Paul Rohan, J.C. (Papal Seminary, Pune, India, 2022)
Literally, theology is a ‘science of God’. Traditionally Christian theology was understood as a discourse on the nature, attributes and existence of a divine God. In the fall of nineteenth century Friedrich Nietzsche (1844-1900), one of the forerunners of the contemporary schools of thought and a radical critic of Western society and culture published an obituary that ‘God is dead’. This was developed as the death of God philosophy and some theologians later formulated the death of God theology. In the background of the announcement ‘God is dead’ the traditional theology as a study about a living God becomes invalid because the God of the traditional theology is no more. Therefore a new theology is urgently envisaged based on a God who involves with the human situations and ‘who dances with the humans’. It will not be a theology about a God captured by a religion, but about a God as such and will be free from the barriers of religions, moral and value systems. It will lead the human beings to a universal spirituality acceptable to all, not a spirituality based on a particular religion.
Keywords: Anti-Christ; Secularization